2012
DOI: 10.1371/journal.pone.0036513
|View full text |Cite
|
Sign up to set email alerts
|

5-HTTLPR Polymorphism Impacts Task-Evoked and Resting-State Activities of the Amygdala in Han Chinese

Abstract: BackgroundPrior research has shown that the amygdala of carriers of the short allele (s) of the serotonin transporter (5-HTT) gene (5-HTTLPR) have a larger response to negative emotional stimuli and higher spontaneous activity during the resting state than non-carriers. However, recent studies have suggested that the effects of 5-HTTLPR may be specific to different ethnic groups. Few studies have been conducted to address this issue.Methodology/Principal FindingsBlood oxygenation level dependent (BOLD) functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 71 publications
(100 reference statements)
1
16
1
Order By: Relevance
“…In Asian population, contrary to the above presented results in the Caucasian population, the result from the resting state demonstrated higher activity in the amygdala of the L/L group compared with that in the S/S group, but no significant difference was found in the emotional task between the two groups (Li et al, 2012). This suggests that the effect of 5-HTTLPR on brain activity may be modulated by ethnic differences.…”
Section: Introductioncontrasting
confidence: 93%
“…In Asian population, contrary to the above presented results in the Caucasian population, the result from the resting state demonstrated higher activity in the amygdala of the L/L group compared with that in the S/S group, but no significant difference was found in the emotional task between the two groups (Li et al, 2012). This suggests that the effect of 5-HTTLPR on brain activity may be modulated by ethnic differences.…”
Section: Introductioncontrasting
confidence: 93%
“…However, the present study can still contribute to revealing the effect of the 5-HTTLPR, as previous studies without such subtypes have elucidated the effects of the 5-HTTLPR [5]. Moreover, a few recent studies have suggested that Asians differ from those of European descent as regards the effects of 5-HTTLPR on amygdala activity [17], [19] and vulnerability to mood disorders [20]. As most of the studies that have examined the effects of 5-HTTLPR on emotion information processing were conducted with participants all or most of whom were of European descent [3], [4], [7], [21] and only a few studies have yet been conducted with Asian populations [15], [17] the current study will provide further data regarding the effects of 5-HTTLPR on emotional functions in the Asian population.…”
Section: Methodsmentioning
confidence: 75%
“…Some recent studies have shown that the low-functioning alleles in Asian populations are linked with lower amygdala activity towards negative information [17] and in a resting state [19] as well as with a lower prevalence of mood disorders [20]. The results have often been linked with the high-functioning alleles rather than the low-functioning alleles in studies conducted with participants who were mostly or solely of European descent [21], [35].…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study advocate for the use of analytic components of BOLD fMRI signals-such as the amplitude envelope-, particularly when studying the genetic influences leading to functional alterations of the amygdala in depression. This may have important implications considering the relevance of genetic factors such as the serotonin transporter genotype (5-HTTLPR) in modulating the amygdala during both resting-state and task-related fMRI paradigms [El-Hage et al, 2013;Li et al, 2012;Munafo et al, 2008]. The present findings suggest that the genetic bases of amygdalar activity may probably be better elicited by examining specific analytical properties of fMRI signals.…”
Section: Familial Factors Altering Amygdalar Centrality In the Depresmentioning
confidence: 76%